2007
DOI: 10.1007/s11274-007-9346-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production by Saccharomyces cerevisiae and Kluyveromyces marxianus in the presence of orange-peel oil

Abstract: Two ethanologenic yeasts, Saccharomyces cerevisiae and Kluyveromyces marxianus, were used to ferment sugar solutions modeling hydrolyzed Valencia orange peel waste at 37°C. Orange stripper oil produced from orange peel was added in various amounts to determine its effect on ethanol production. The minimum peel oil concentration that inhibited ethanol production was determined after 24, 48 and 72 h and the two yeasts were compared to one another in terms of ethanol yield. Minimum inhibitory peel oil concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 16 publications
2
47
0
3
Order By: Relevance
“…Additionally, it was concluded that limonene (84.2%) and linalol (% 3.54) which was found in high concentrations in the composition of EO CVV along with low concentrations of α-pinenen (0.47%), and the high acidity of EO CVV (pH 3.13) may have contributed to the increased antimicrobial activity. In previous studies, it has been found that limonene in the composition of EO CVV has antifungal properties and that limonene, α-pinene and linalool have strong antimicrobial effects (Wilkins et al, 2007). The results regarding the antimicrobial activity of EO CVV in our study are compatible with other studies on different orange cultivars (Fisher & Phillips, 2006;Pengelly, 2004;Rahman et al, 2010;Subba et al, 2006;Tepe et al, 2005).…”
Section: Resultssupporting
confidence: 91%
“…Additionally, it was concluded that limonene (84.2%) and linalol (% 3.54) which was found in high concentrations in the composition of EO CVV along with low concentrations of α-pinenen (0.47%), and the high acidity of EO CVV (pH 3.13) may have contributed to the increased antimicrobial activity. In previous studies, it has been found that limonene in the composition of EO CVV has antifungal properties and that limonene, α-pinene and linalool have strong antimicrobial effects (Wilkins et al, 2007). The results regarding the antimicrobial activity of EO CVV in our study are compatible with other studies on different orange cultivars (Fisher & Phillips, 2006;Pengelly, 2004;Rahman et al, 2010;Subba et al, 2006;Tepe et al, 2005).…”
Section: Resultssupporting
confidence: 91%
“…Many studies of K. marxianus have been carried out in liquid culture to investigate biomass or enzyme production [11][12][13][14][15][16][17][18]. However, although the potential applications are numerous, there have been few studies in solid-state culture (SSC), e.g., the production of inulinase [19], the production and optimisation of aroma compounds using factorial design and surface response methodology [20,21], and the production of inulinase and its preliminary characterization using factorial design [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These bioactive compounds comprise approximately 0.1-0.5% of citrus peel dry weight. The major carotenoids available in citrus are α-and β-carotene, lutein, zeaxanthin and β-cryptoxanthin, which are known to be responsible for a wide range of functional properties, mainly offering protection against the reactive oxygen species damaging actions at the cellular level [64,[82][83][84]]. …”
Section: Carotenoidsmentioning
confidence: 99%